ARIA digital anamorphosis: Digital transformation of health and care in airway diseases from research to practice. Issue 1 (23rd October 2020) - Bousquet, Jean; Anto, Josep M.; Bachert, Claus; Haahtela, Tari; Zuberbier, Torsten; Czarlewski, Wienczyslawa; Bedbrook, Anna; Bosnic‐Anticevich, Sinthia; Walter Canonica, G.; Cardona, Victoria; Costa, Elisio; Cruz, Alvaro A.; et al.
Abstract: Digital anamorphosis is used to define a distorted image of health and care that may be viewed correctly using digital tools and strategies. MASK digital anamorphosis represents the process used by MASK to develop the digital transformation of health and care in rhinitis. It strengthens the ARIA change management strategy in the prevention and management of airway disease. The MASK strategy is based on validated digital tools. Using the MASK digital tool and the CARAT online enhanced clinical framework, solutions for practical steps of digital enhancement of care are proposed.